Treatment-Responsive Granulomatous-Lymphocytic Interstitial Lung Disease in a Pediatric Case of Common Variable Immunodeficiency - Tillman, Robert; Guillerman, R. Paul; Trojan, Timothy; Silva-Carmona, Manuel; Chinn, Ivan K. (Frontiers in Pediatrics, 2019)
Granulomatous-Lymphocytic Interstitial Lung disease (GLILD) is a granulomatous and lymphoproliferative condition occurring in approximately 25% of Common Variable Immunodeficiency (CVID) patients with the highest prevalence in the late teen to young adult years. GLILD was first described in adults and carries a poor prognosis with survival estimated to be reduced by half. Here we report a pediatric case of CVID-associated GLILD that presented with rapid deterioration over 3 months and responded to adult-based treatment with dual chemotherapeutic agents (rituximab and azathioprine), resulting in complete resolution of clinical findings and near complete resolution of radiologic findings. This case highlights the opportunity to achieve a favorable outcome in GLILD following appropriate diagnosis and therapy.